Proposed Marketing Strategy to Increase the Penetration of Livin’ by Mandiri through Strategic Partnership Program - Mangngalle, Riska Indriyani; Aprianingsih, Atik (SEIKO : Journal of Management & Business, 2023)
PT Bank Mandiri (Persero) Tbk launched Super App Livin’ by Mandiri on October 2nd 2021, replace the old version of their mobile banking namely Mandiri Online (Livin’ 1.0). In 2022, the management of Bank Mandiri arranged the target users of Livin’ by Mandiri and distributed it to 12 Regional Offices across Indonesia. To achieve the target of Livin’s user, Bank Mandiri Region VI/Jawa 1 conducted several acquisition program, one of them is Strategic Partnership Program. From 131 partners that has been joined the strategic partnership program in 2022, 106 partners are categorized as low acquisition because they only can acquired 500 users. This study aims to examine the proposed solutions to increase willingness of partner to distribute Livin’ by Mandiri, so at the end the penetration of Livin’ by Mandiri can be increased. The findings reveal that there are some problems which experienced by partner when distribute Livin’ by Mandiri, such as technical issues, lack of product knowledge, partner has staff limitation, gimmick does not meet partner’s preferences, promo has not been optimized, partners need reward and recognition program, and unconfident of partner to distribute Livin’ by Mandiri. The study concludes that to increase willingness partner to acquire Livin’s users, they need offline training, customization of gimmicl, reward and recognition program, and accelerated referral fee payment. Future research will be need to explore the affect of these recommendations. KEYWORDS: Strategic Partnership, Livin’ by Mandiri, Motivational Channel Members